2023
DOI: 10.1371/journal.pone.0293897
|View full text |Cite
|
Sign up to set email alerts
|

Lambs supplemented with Amazonian oilseed co-products: Meat quality and fatty acid profile

Vinícius Costa Gomes de Castro,
Juliana Cristina de Castro Budel,
Thomaz Cyro Guimarães de Carvalho Rodrigues
et al.

Abstract: The Amazon has a wide variety of oilseeds that generate a huge amount of co-products with potential for use in animal nutrition. The objective was to use alternative resources (oilseed cakes) in the feeding of lambs to assign a sustainable destination to this biomass, and evaluate its influence on the quality and fatty acid (FA) profile of the meat. Twenty-four lambs, male, castrated, crossbred Dorper × Santa Inês, weighing 30 ± 1.3 kg of initial body weight, were distributed in a completely randomized design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…In a more recent study, de Castro et al [ 146 ] found that incorporating oilseed cakes into the diets of lambs had significant effects on the lipid and protein composition of meat, specifically in the Longissimus lumborum . The inclusion of oilseed cakes resulted in decreased cooking losses and influenced various color parameters, such as L*, a*, b*, chroma, and hue angle.…”
Section: Alternative Feed Resources and Small Ruminants’ Product Qualitymentioning
confidence: 99%
“…In a more recent study, de Castro et al [ 146 ] found that incorporating oilseed cakes into the diets of lambs had significant effects on the lipid and protein composition of meat, specifically in the Longissimus lumborum . The inclusion of oilseed cakes resulted in decreased cooking losses and influenced various color parameters, such as L*, a*, b*, chroma, and hue angle.…”
Section: Alternative Feed Resources and Small Ruminants’ Product Qualitymentioning
confidence: 99%